2021
DOI: 10.1111/joss.12648
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profile of protected designation of origin water buffalo ricotta cheese by different sensory methodologies

Abstract: The disciplinary protocol of protected designation of origin (PDO) water buffalo ricotta cheese allows to use both different ingredients and production technologies. This does not allow having a straight sensory profile. This study aimed to characterize the sensory profile of different PDO water buffalo ricotta cheeses and compare them with cow and sheep ricotta cheeses. To this purpose, a classical descriptive analysis (DA) and the modified version of flash profile (mFP) were used to draw the sensory profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…The low spreadability of PSR could be related to the higher TS content and consequently lower moisture content of the product compared with ISR. This agreed with several authors, who reported that higher moisture in Ricotta cheese resulted in higher spreadability attributes (Miele et al 2021;Rubel et al 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The low spreadability of PSR could be related to the higher TS content and consequently lower moisture content of the product compared with ISR. This agreed with several authors, who reported that higher moisture in Ricotta cheese resulted in higher spreadability attributes (Miele et al 2021;Rubel et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This agreed with several authors, who reported that higher moisture in Ricotta cheese resulted in higher spreadability attributes (Miele et al . 2021; Rubel et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Miele ve ark. [38] manda, koyun ve inek sütünden üretilen peynirlerden arta kalan peynir altı suları ile üretilmiş 8 farklı menşei işaretine sahip Ricotta peynirinin duyusal özelliklerini incelemişlerdir. Çalışma sonucunda; manda peynirinden elde edilen peynir altı suyu ile üretilen Ricotta peynirlerinin düşük tatlı tat özelliği ile birlikte yoğun süt aromasına sahip olduklarını belirlemişledirler.…”
Section: Ricotta Peyniriunclassified
“…Ricotta (literally meaning “cooked again”), which is not considered a cheese by the Italian law but a different kind of dairy product, is obtained by heat-induced coagulation (at 85–90 °C) of whey proteins (albumin and globulin) after the addition of acidifying agents, usually lemon or vinegar [ 1 , 2 ]. This process generates a curd of modest consistency incorporating the fats that after floating are transferred to draining moulds, cooled, and finally packaged.…”
Section: Introductionmentioning
confidence: 99%
“…Dairy products designed as PDO, because of their higher commercial value compared to ordinary products, are potential targets of fraudulent adulterations, including the above-mentioned mislabelling of whey origin. Although it is known that the kind of whey primarily affects the sensorial properties of the ricotta whey cheeses [ 2 ], several additional factors, such as the local know-how adopted in processing [ 8 ], the breed of dairy animals and their diet [ 9 , 10 ] contribute to conferring their own distinctive origin-related uniqueness to products designed as PDO. PDO Ricotta Romana, for instance, is obtained from full-fat sheep whey provided by the commonest breeds in the Lazio Region.…”
Section: Introductionmentioning
confidence: 99%